Dissemination of Shanxi Mountain songs - Zhihong, Wang; Mohamed Razali, Camellia Siti Maya; Musib, Ahmad Faudzi (Human Resources Management Academic Research Society (HRMARS), 2024)
The purpose of this study is to investigate three genres of Shanxi mountain songs: Shanqu, Kaihuadiao, and Juanxipian in terms of their current dissemination, channels and media, and to measure the differences in the dissemination of the three genres. For the purpose of this study, an online questionnaire was designed and conducted and a total of 435 samples were responded to. The results of this study show that respondents' familiarity with and popularity of the three genres of Shanxi mountain songs are low, and the audience's knowledge of Shanxi mountain songs is generally weak. Respondents accessed information about the three genres of Shanxi mountain songs more from communication channels like cultural events and educational environments, and from traditional media like television programmes. In addition, the feedback from the respondents clarified the situation that there are differences in the dissemination of the three genres of Shanxi mountain songs. In conclusion, the survey report on the dissemination of the three genres of Shanxi mountain songs will help to provide data support for the development of subsequent studies on the dissemination of Shanxi mountain songs.